Analisis Pengaruh Kualitas Pelayanan, Harga Dan Lokasi Terhadap Keputusan Pembelian Di Kedai CS Warung Kopi Mendungan Kartasura - Widayanti, Arti; , Drs. M. Nasir, M.M (2015)
This study has the objective to analyze the influence of service quality, price, and location on purchasing decision in a selected coffee shop. Furthermore, this study is a casual research which examines the causal relationships between dependent variable (purchasing decision), and independent variables (service quality, price, and location). Using survey method for the data collection, this study involved 100 customers who come in Kedai CS Warung Kopi as the research samples. Analytical methods used in this research are quantitative analysis of multiple regression analysis. This analysis includes: validity, reliability, and normality, multiple regression analysis, hypothesis testing by t test and F test, and R square (R2). According to the result of the analysis, service quality (X1) and price (X2) influence positively and significantly on the purchasing decision, while location (X3) does not influence positively and ignificantly on the purchasing decision. Hereafter, the F test shows that there is a simultant effect between quality service, price, and location toward purchasing decision, proved by significance level valued at 0,000 < 0,05. Rated R square (R2) obtained at 0,429. This means that the variation of the variable changes in the purchasing decision can be explained by the variable quality of service (X1), price (X2), location (X3) amounted to 42,9%. Last but not least, the most dominant variable to influence the purchasing intention in Kedai CS Warung Kopi is service quality (X1) proved by regression score valued at 0,508.